Pengaruh Pengungkapan Green Intellectual Capital dan Sustainabillity Reporting Disclosure Terhadap Kinerja Perusahaan - Andreas Koli Koli Todo Golo; Christina Dwi Astuti (Peneliti.net, 2023)
The purpose of this research is to examine and analyze the effect of Green Intellectual Capital Disclosure and Sustainability Reporting Disclosure on Company Performance. The research population is Primary Sub-Sector Companies listed on the Indonesia Stock Exchange during 2019-2021. The type of data used is secondary data, namely data derived from financial reports and annual reports. The purposive sampling method used in this study obtained 54 samples and a total sample of 162 companies from 2019-2021. This study uses the Multiple Linear Regression model. The results of this study indicate that Green Intellectual Capital has a positive effect on company performance and Sustainability Reporting Disclosure has no effect on company performance